The derivative field of subconcept ΑΣΘΕΝΕΙΑ in Ancient Greek - Мартин, Володимир Орестович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The concept “DISEASE” in ancient Greek language is realized with subconcepts ΝΟΣΟΣ, ΑΡΡΩΣΤΙΑ, ΑΣΘΕΝΕΙΑ, which were formed in different times. In the article the derivative field of subconcept ΑΣΘΕΝΕΙΑ in ancient Greek language has been analyzed. As the result of investigation the circle of derivates that were made from the primal stem *σθεν- has been established, their structure has been analyzed and the following conclusion has been made – the majority of lexemes are characterized by the presensce of alpha privativum. The perception of the ancient Greeks of the disease as a lack of physical strength contributed to the fact that, in conjunction with alpha privativum, the stem σθεν- gave the beginning to the lexemes denoting a morbid condition in general, which makes it possible to distinguish ασθεν- as the base for the majority of them (except σθενοβλαβής). A number of lexemes have been formed from this base such as nouns, adjectives, adverbs, verbs. Derivative analysis of words with the primal stem *σθεν- with the meaning of a morbid condition has allowed to establish the following:1) from the primal stem 15 words had been made, most of them (14 words) are characterized with alpha privativum; 2) one word (ἀσθενής) is a pure stem and 7 words had been formed with suffixes and the rest had been formed according to the stem formation; 3) the semantics of the derivates has been characterized with the meaning of the stem – “strength absence”, which soon transformed into “disease”, “misery”; 4) all the derivatives save maximally semantic connection with the primal stem. On the basis of conceptual and derivative analysis the frame structure of this concept has been established.